Pendidikan dan Bimbingan Anak Berkebutuhan Khusus (ABK) Disleksia - Darmayanti, Nefi; Hayati, Nurlaila; Rohali, Alia; Marpaung, Zulham Efendi (Intitut Agama Islam Nasional Laa Roiba Bogor, 2024)
The purpose of this study is to understand the teaching and learning process in inclusive schools for dyslexic students and the ability of students with special needs to receive instruction using methods implemented in schools, as well as to understand the efforts of teachers in motivating dyslexic children. This research uses a qualitative research approach. It is descriptive research, with data sources from observations, interviews, and documentation. The data obtained will be analyzed qualitatively and presented in descriptive form. The research findings indicate that the teaching and learning process in inclusive schools for dyslexic students is still equated with normal children, using the 2013 curriculum. Therefore, students with special needs, including dyslexia, need additional guidance from supervising teachers provided by the inclusive school. Guidance from teachers, such as repeating the alphabet, arranging letter cards into words or sentences, and repeating words in reading, greatly helps dyslexic children in overcoming reading difficulties. The motivation from teachers makes dyslexic students more enthusiastic in following guidance and instructions from teachers.